Empiric Addition of Quinolones to First-Line Tuberculosis Treatment Is Associated With Increased Odds of XDR-TB - Udwadia, Zarir F.; Patel, Palak P.; Sharma, Samridhi; Gupta, Amita; Tornheim, Jeffrey A. (Frontiers in Tropical Diseases, 2022)
Background Multidrug-resistant tuberculosis (MDR-TB) represents a significant clinical and public health challenge worldwide. Out of concern for possible resistance, some providers prescribe first- and second-line tuberculosis treatment together before completing drug susceptibility testing (DST), which may increase emergent resistance. Methods MDR-TB patients at an Indian referral center were enrolled in an observational cohort. Participants with drug susceptibility test (DST) results were categorized as prescribed fluoroquinolones, streptomycin, both, or neither with first-line treatment before DST. Odds of additional resistance to fluoroquinolones and aminoglycosides (XDR-TB) were calculated in association with empiric combined first- and second-line treatment before DST. Results Of 494 participants, 130 (26.3%) received a fluoroquinolone or streptomycin with first-line drugs before DST. Odds of XDR-TB were associated with fluoroquinolone prescription before DST [odds ratio (OR): 2.19, 95% confidence interval (CI): 1.26–3.76). The association with XDR-TB persisted in multivariable analysis (adjusted OR: 2.43, 95% CI: 1.19-4.91). Combined empiric first- and second-line treatment before DST was not associated with eventual outcomes. Conclusion Many participants received empiric combined first- and second-line drugs before DST, which was associated with XDR-TB. To minimize emerging resistance, treatment-associated side effects, and provide the best possible care, this approach should be discouraged in favor of early DST and DST-guided TB treatment.